2015
DOI: 10.2807/1560-7917.es2015.20.23.21154
|View full text |Cite
|
Sign up to set email alerts
|

Community-acquired infections due to Staphylococcus argenteus lineage isolates harbouring the Panton-Valentine leucocidin, France, 2014

Abstract: We describe two cases of human infections caused by Staphylococcus aureus clonal complex (CC) 75, also called Staphylococcus argenteus, harbouring the Panton-Valentine leucocidin (PVL). These two sporadic cases were community-acquired, and identified in France in 2014. Both had an epidemiological link with Mayotte, an overseas department of France located in the Indian Ocean off the south-eastern African coast. This report illustrates that, contrary to previous descriptions, S. argenteus can acquire important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 16 publications
1
50
0
Order By: Relevance
“…In our present study, five isolates of coa -XIb (4.5% among apparent S. aureus carriers) were revealed to be S. argenteus , elucidating the distribution of S. argenteus among healthy individuals for the first time. ST2250, which was identified in Myanmar in this study, was also described in France, Belgium, and Thailand [ 48 , 49 , 50 ]. Although PVL genes were rarely detected [ 48 ], only two S. argenteus isolates in France belonging to ST2250 and ST2277 were revealed to harbor pvl [ 49 ].…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In our present study, five isolates of coa -XIb (4.5% among apparent S. aureus carriers) were revealed to be S. argenteus , elucidating the distribution of S. argenteus among healthy individuals for the first time. ST2250, which was identified in Myanmar in this study, was also described in France, Belgium, and Thailand [ 48 , 49 , 50 ]. Although PVL genes were rarely detected [ 48 ], only two S. argenteus isolates in France belonging to ST2250 and ST2277 were revealed to harbor pvl [ 49 ].…”
Section: Discussionmentioning
confidence: 79%
“…The type strain of S. argenteus , MSHR1132, a blood isolate in Australia, lacks pigment production genes, and has a nucA gene distinctive from S. aureus , as well as CRISPR element inserted into orfX [ 24 , 25 ]. After the first recognition of CC75 as S. argenteus , various STs have been reported to date, and this species has been isolated in New Zealand, Asia (Cambodia, Thailand, China), Europe (France, Belgium), Fiji, French Guiana, and Trinidad and Tobago [ 26 , 48 , 49 , 50 ]. A retrospective study in Thailand indicated that S. argenteus accounted for 4.1% of isolates originally identified as S. aureus [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…The virulence potential of S. argenteus is interesting and so far, conflicting results have been published. Actually, communityacquired Australian S. argenteus isolates with and without SCCmec type IV have been isolated primarily from skin infections (McDonald et al, 2006;Tong et al, 2010), and seemed less likely to be involved in sepsis (Tong et al, 2010) and showed reduced virulence in mice (Tong et al, 2013), although two severe infections with strains that had acquired PVL toxin have been described in France (Dupieux et al, 2015). A recent study from Thailand showed that as much as 19% of community-onset invasive sepsis cases in Thailand were infected with this species.…”
Section: Discussionmentioning
confidence: 99%
“…At first, S. argenteus was thought to be less virulent than S. aureus, due to the lack of the yellow pigment staphyloxantin [11], which confers resistance against oxidative stress and neutrophil killing [12]. Indeed, S. argenteus was later shown to be more susceptible to oxidative stress and neutrophil killing in vitro than S. aureus and had reduced virulence in murine sepsis and skin infection models [2,3,13], although this was not connected to the deficient staphyloxantin expression [9]. However, as compared to S. aureus, similar [3,6] or even higher [14] human mortality rates have been reported for S. argenteus.…”
Section: Introductionmentioning
confidence: 99%